Checkpoint trust evaluation method based on Markov - Jun-feng TIAN; Ya-jiao ZHANG (Tongxin xuebao)
According to the trust evaluation of software and its modules after running for a period of time a checkpoint trust evaluation model was presented based on Markov to find the vulnerability of software by monitoring software behavior dynamically.The model reflected the software running situation by some checkpoints worked in the software behavior trace,then divided some trust levels to reflect the checkpoint trusted situation by the Markov model and the weight of checkpoint,and finally synthesized the checkpoint trusted situation to determine the software trust value.Experimental results showed that the model could effectively reflect the trusted situation of the various parts of the software,and verify the rationality and availability of the model.